(untitled) (British Journal of Multidisciplinary and Advanced Studies, 2024)
This research paper investigates the ethical considerations and impact of the Russo-Ukraine war on the food and energy supply chain in Nigeria. Against the backdrop of the geopolitical tensions, the study aims to assess the ethical dimensions surrounding the global supply chain disruptions emanating from the conflict and their consequences with ethical re-evaluation on the policymakers. Employing a comprehensive methodology that combines literature review, documentary data analysis, and case studies, the research sheds light on the ethical dilemmas faced by stakeholders in the Nigerian supply chain. The findings reveal the vulnerabilities and disruptions caused by the war, affecting the ethical sourcing, distribution, and pricing of essential goods in the Nigerian market.The implications of these disruptions extend to the ethical considerations within the global supply chain and Nigeria’s resilience in the face of external shocks. The paper discusses potential strategies to address ethical challenges, enhance supply chain resilience, and ensure the ethical and sustainable flow of food and energy resources in the aftermath of the Russo-Ukraine conflict. In conclusion, this research contributes to the understanding of the ethical dimensions of supply chain disruptions caused by geopolitical events. The outcomes provide valuable insights for policymakers, industry stakeholders, and researchers interested in navigating these challenges associated with global crises and their impact on developing economies like Nigeria.